Engineering biotic stress tolerance via CRISPR-Cas mediated genome editing in crop plants - Amjad Hussain; Mamoona Munir; Awais Khalid; Musrat Ali; Mohammed Amanullah; Qurban Ali; Hakim Manghwar (Plant Stress)
Plants are incessantly challenged by a plethora of plant pests and pathogens, putting global agricultural productivity and food security at stake. Over several decades, various strategies have been developed in agriculture to overcome plant diseases and insect pests. With chemical control that remains effective but involves severe ecological and environmental concerns, conventional and transgenic breeding strategies have been primarily deployed to generate new varieties with novel genetic mutations. Though these strategies present a pivotal role in plant development, in part, they normally include extensive and labor-intensive processes. CRISPR-Cas technology, a genome editing tool, has opened new avenues to accelerate plant breeding by creating disease and pest resistance in a wide range of plants. CRISPR-Cas revolutionized agriculture by limiting yield losses due to biotic stress and minimizing reliance on pesticide usage. Here, we summarize the advances of CRISPR-Cas technology and the applications of this technology in disease and pest resistance development in crop plants. In addition, the review also discusses the advantages and concerns of CRISPR-Cas genome editing in crop plants.